In Vitro Cell Culture of Rhus coriaria L.: A Standardized Phytocomplex Rich of Gallic Acid Derivatives with Antioxidant and Skin Repair Activity - Giovanna Pressi; Oriana Bertaiola; Chiara Guarnerio; Elisa Barbieri; Giovanna Rigillo; Paolo Governa; Marco Biagi; Flavia Guzzo; Alessandra Semenzato (Cosmetics, 2022)
This study focused on the biological evaluation and chemical characterization of a new ingredient obtained by in vitro cell culture of Rhus coriaria L. An in vitro plant cell culture method permits to cultivate plant in a short period of time and to obtain extract with a high safety profile for the consumer, free from heavy metals, pesticides, aflatoxins, bacterial or fungal contamination. Through the selection of specific cell culture media, it was possible to obtain a Rhus coriaria cell line with a high content of gallic acid derivatives. The Rhus coriaria L. phytocomplex (RC-P), containing 7.6% w/w of acid gallic derivatives, was obtained by drying of plant cell biomass after 14 days of growth in the final selected culture medium. UPLC-ESI-MS and UPLC-DAD analysis allowed to identify numerous gallic acid derivatives, such as galloyl hexose, trigalloyl hexose and high molecular weight galloyl derivatives, and to quantify their overall content. The antioxidant activity of the RC-P was tested by DPPH assay and the wound healing activity was evaluated using a scratch wound healing test on human keratinocytes and fibroblasts. This work showed that RC-P could be a new effective cosmetic ingredient with antioxidant and skin repair activity.